HPLC-MS Analysis and Antioxidant Activity Assessment of Moringa oleifera Leaf Extrac t: Identification of Bioactive Compounds and Therapeutic Potential (International Journal of Scientific Research in Science and Technology, 2025)
This study presents a comprehensive HPLC-MS analysis and antioxidant activity evaluation of Moringa oleifera leaf extract, a medicinal plant renowned for its nutritional and therapeutic properties. Fresh Moringa leaves were collected, processed through shade drying, and extracted using methanol through maceration followed by liquid-liquid extraction. High-performance liquid chromatography coupled with mass spectrometry (HPLC-MS) was employed to identify and quantify bioactive compounds. The analysis revealed the presence of 15 major compounds including quercetin, kaempferol, chlorogenic acid, rutin, caffeic acid, ferulic acid, and gallic acid. Phytochemical screening confirmed the presence of flavonoids, phenolic compounds, alkaloids, and saponins in varying concentrations across different extraction solvents. Antioxidant activity assessment using DPPH and ABTS assays demonstrated significant free radical scavenging capacity with IC₅₀ values of 89.5 μg/mL and 76.3 μg/mL respectively. The methanol extract showed superior antioxidant activity compared to other solvent extracts, correlating with higher flavonoid and phenolic content. These findings support the traditional use of Moringa oleifera in folk medicine and provide scientific basis for its development into pharmaceutical formulations and functional foods.